2020
DOI: 10.1111/jfpp.14397
|View full text |Cite
|
Sign up to set email alerts
|

Use of agro‐industrial residues as potent antioxidant, antiglycation agents, and α‐amylase and pancreatic lipase inhibitory activity

Abstract: Agro‐industrial residues are a potential source of bioactive compounds. This research is focused on the extraction of phenolic compounds from agro‐industrial residues produced in large scale in Brazil (peanut and grape marc), as well as to evaluate their antioxidant activity and ability to inhibit glycation reactions and digestive enzymes. As glycation is the main spontaneous cause of protein damage and is involved in the progression of diseases such as diabetes and obesity. The results showed that the major p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 83 publications
(122 reference statements)
0
15
0
Order By: Relevance
“…The data for the double combination samples is presented in Figure S2b. Similarly, polyphenol-rich extracts of Syzygium cumini [74], peanut skin and grapes [73], and brown algae [65] were shown to exhibit higher antiglycation activity in the BSA-FRU than the BSA-MGO model. The combination samples all exhibited antagonistic interactions towards the inhibition of BSA glycation by FRU (Table S2).…”
Section: Antioxidant Activity-advanced Glycation End-products (Ages)mentioning
confidence: 96%
See 1 more Smart Citation
“…The data for the double combination samples is presented in Figure S2b. Similarly, polyphenol-rich extracts of Syzygium cumini [74], peanut skin and grapes [73], and brown algae [65] were shown to exhibit higher antiglycation activity in the BSA-FRU than the BSA-MGO model. The combination samples all exhibited antagonistic interactions towards the inhibition of BSA glycation by FRU (Table S2).…”
Section: Antioxidant Activity-advanced Glycation End-products (Ages)mentioning
confidence: 96%
“…Data for the double combination samples is presented in Figure S2a. Considering extracts as examples for polyphenol mixture samples, several polyphenol-rich plant extracts have been previously shown to exhibit antiglycation activity [72][73][74][75]. The antiglycation activity of the non-encapsulated combinations exhibited antagonistic interactions and changed to additive interactions with regards to the antiglycation activity following encapsulation (Table S2).…”
Section: Antioxidant Activity-advanced Glycation End-products (Ages)mentioning
confidence: 99%
“…In addition, flavonoids have been recognized to interfere with the α-amylase activity by forming covalent bonds with starch during cooking and in the stomach, decreasing its availability as a substrate for the enzyme (Takahama & Hirota, 2018 ). Procyanidins of grape seeds are responsible for presenting health-promoting effects such as antioxidant and antihyperglycemic by inhibiting α-amylase and α-glucosidase enzymes (Fernandes et al, 2020a ; Takahama & Hirota, 2018 ; Yilmazer-Musa et al, 2012 ). These compounds are polymers of flavan-3-ols, which are formed exclusively by catechin and/or epicatechin units (Álvarez et al, 2012 ).…”
Section: Grape Pomace As α-Amylase and α-Glucosidase Inhibitorsmentioning
confidence: 99%
“…All the phenolic compound classes showed inhibition of the enzymes with the greatest effect being from the free phenols and the least by the insoluble bound compounds. Along with white grape pomace, peanut skins were investigated for their ability to inhibit the enzymes, α-amylase, and pancreatic lipase to propose applications for agricultural waste materials [87]. Peanut skins were extracted with ethanol using sonication, filtered, and lyophilized for analysis.…”
Section: Enzyme Inhibitionmentioning
confidence: 99%
“…Sixteen adults ingested 2 capsules twice a day for 6 weeks. Other studies have shown peanut skin extracts inhibit α-amylase [85,87], so it was hypothesized that ingestion of peanut skin extracts would influence fasting blood glucose and body fat deposition. Although none of the subjects suffered from either type 1 or type 2 diabetes, some did have abnormal fasting blood glucose levels.…”
Section: Food Applicationsmentioning
confidence: 99%